Use of in vitro derived human neuronal models to study host-parasite interactions of Toxoplasma gondii in neurons and neuropathogenesis of chronic toxoplasmosis - Halonen, Sandra K. (Frontiers in Cellular and Infection Microbiology, 2023)
Toxoplasma gondii infects approximately one-third of the world’s population resulting in a chronic infection with the parasite located in cysts in neurons in the brain. In most immunocompetent hosts the chronic infection is asymptomatic, but several studies have found correlations between Toxoplasma seropositivity and neuropsychiatric disorders, including Schizophrenia, and some other neurological disorders. Host-parasite interactions of bradyzoites in cysts in neurons is not well understood due in part to the lack of suitable in vitro human neuronal models. The advent of stem cell technologies in which human neurons can be derived in vitro from human induced pluripotent stem cells (hiPSCs) or direct conversion of somatic cells generating induced neurons (iNs), affords the opportunity to develop in vitro human neuronal culture systems to advance the understanding of T. gondii in human neurons. Human neurons derived from hiPSCs or iNs, generate pure human neuron monolayers that express differentiated neuronal characteristics. hiPSCs also generate 3D neuronal models that better recapitulate the cytoarchitecture of the human brain. In this review, an overview of iPSC-derived neurons and iN protocols leading to 2D human neuron cultures and hiPSC-derived 3D cerebral organoids will be given. The potential applications of these 2D and 3D human neuronal models to address questions about host-parasite interactions of T. gondii in neurons and the parasite in the CNS, will be discussed. These human neuronal in vitro models hold the promise to advance the understanding of T. gondii in human neurons and to improve the understanding of neuropathogenesis of chronic toxoplasmosis.